A call for a round robin study of XAFS stability and platform dependence at synchrotron beamlines on well defined samples. (29th May 2018) - Chantler, Christopher T.; Bunker, Bruce A.; Abe, Hitoshi; Kimura, Masao; Newville, Matthew; Welter, Edmund
Abstract : A program and methodology are proposed to study X‐ray absorption fine structure of potential reference samples across XAS beamlines and synchrotron facilities, to enable each beamline to cross‐calibrate, provide representative benchmarks and to enable more productive collaborative cross‐facility activities. Abstract : Round robin studies have been used across fields of science for quality control testing and to investigate laboratory dependencies and cross‐platform inconsistencies as well as to drive forward the improvement of understanding of experimental systems, systematic effects and theoretical limitations. Here, following the Q2XAFS Workshop and Satellite to IUCr Congress 2017 on `Data Acquisition, Treatment, Storage – quality assurance in XAFS spectroscopy', a mechanism is suggested for a suitable study across XAFS (X‐ray absorption fine‐structure) beamlines and facilities, to enable each beamline to cross‐calibrate, provide representative test data, and to enable collaborative cross‐facility activities to be more productive.